Structural Modeling of Hope Based on Time Perspective Components with the Mediating Role of Perceived Social Support in Students - Ghahremanzadeh Aghabagher, Vahed; Mehrinejad, Seyed Abolghasem; Sotodehasl, Nemat; Asadzadeh Dahraei, Hassan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the structural relationships between time perspective dimensions and hope for life in university students, focusing on the mediating role of perceived social support.Methods and Materials: The research employed a descriptive–correlational design using structural equation modeling. The statistical population comprised university students in Tehran during the 2019–2020 academic year, from which 584 participants (55.1% female, 44.9% male) were selected through multistage random cluster sampling. Participants completed the Zimbardo Time Perspective Inventory (ZTPI), Snyder’s Adult Hope Scale, and the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis was conducted using SPSS and AMOS software. Model fit was evaluated with χ²/df, CFI, TLI, and RMSEA indices. The mediating effects of perceived social support were tested through bootstrapping with 5,000 resamples at a 95% confidence interval.Findings: Results indicated that Past-Negative (β = –0.034, p < 0.01) and Past-Positive (β = 0.035, p < 0.01) orientations indirectly predicted agency thinking via perceived social support. Present-Fatalistic orientation had a direct negative effect on both agency (β = –0.149, p < 0.05) and pathways thinking (β = –0.141, p < 0.01). Present-Hedonistic orientation indirectly predicted agency (β = 0.101, p < 0.01) and pathways thinking (β = –0.045, p < 0.01) through perceived social support. Future-Goal-Oriented perspective had a direct positive effect on pathways thinking (β = 0.262, p < 0.01).Conclusion: The findings highlight that time perspective dimensions influence hope for life both directly and indirectly through perceived social support. Positive temporal orientations, when supported by strong social networks, enhance motivational and strategic components of hope, while negative orientations, particularly Present-Fatalistic, undermine these aspects.